Evaluation of accounting research: The criteria of the main brazilian journals - Ferreira, Mônica Aparecida; Carvalho, Hugo Leonardo Menezes de; Lemes, Sirlei; Farias, Manoel Raimundo Santana (Seven Editora, 2023)
Considering the evaluation phase as an important stage for the scientific area development and knowledge dissemination, this study aims to verify the criteria established by the main accounting journals in the evaluation process of the researches developed in Brazil. In order to do so, we used the existing instructions regarding the evaluation process of the studies sent to all "A" Qualis / Capes stratum and a journal of each lower stratum "B1", "B2" and " B3 " journals from the Accounting area. Thus, it was possible to identify the criteria, their definitions and also to make a comparative between the analyzed journals by which has been demonstrated the lack of uniformity in the criteria transparency, the objectives expected by them, and an evaluative isomorphism by the replication of the stratum criteria "A "Qualis / Capes by the magazines of stratum" B1 ", " B2 "and" B3 ". These results indicate, from the epistemological point of view, an as undeveloped stage of evolution yet in this aspect of the evaluation, as well as contribute to a better understanding of the form of occurrence of the Brazilian accounting research evaluation process, presented by the journals in their evaluation. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-138